Experimental Investigation on Effect to the Specific Strength of FDM Fabrication Parameters Using Taguchi Method - Sedat İriç (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The Fused Deposition Modeling (FDM) fabrication is commonly used printing technique, the reasons behind this are low consumable cost, simplicity of workflow and more reliable. The quality of the printed parts depends on various process variables such as part orientation, layer thickness, hotend and bed temperature, fabricating speed, infill pattern and infill density, number of top-bottom solid layers, number of shells etc. Literature suggests that infill density, number of shells and number of top-bottom solid layers are variables that changing the tensile strength under tension of 3D fabricated parts and also have effect on weight of the parts. This study focuses on effect of infill density (ID), number of shells (NS) and top-bottom solid layers (TBSL) on specific strength (strength/weight ratio). Taguchi L18 Orthogonal Array (OA) design is used to perform the experiments. 18 runs with 3 repeated specimens were printed according to the ASTM D638 Type I standard using different printing variables. According to the results, parameters increase of ID, NS and TBSL were seen to effect significant improvement in the specific strength increase. However, between 40-60% ID has negative effect to specific strength while NS and TBSL increase.